Oscillations in the stochastic gravitational wave background from sharp features and particle production during inflation - Fumagalli, Jacopo; Renaux-Petel, Sébastien; Witkowski, Lukas T. (Journal of cosmology and astroparticle physics, 2021)
We identify a characteristic pattern in the scalar-induced stochastic gravitational wave background from particle production during inflation. If particle production is sufficiently efficient, the scalar power spectrum exhibits $\mathcal{O}(1)$ oscillations periodic in $k$, characteristic of a sharp feature, with an exponentially enhanced envelope. We systematically study the properties of the induced spectrum of gravitational waves sourced after inflation and find that this inherits the periodic structure in $k$, resulting in a peak in the gravitational wave energy density spectrum with $\mathcal{O}(10 %)$ modulations. The frequency of the oscillation in the scalar power spectrum is determined by the scale of the feature during inflation and in turn sets the frequency of modulations in the gravitational wave signal. We present an explicit realisation of this phenomenon in the framework of multifield inflation, in the form of a strong sharp turn in the inflationary trajectory. The resulting stochastic background is potentially detectable in future gravitational wave observatories, and considerations of backreaction and perturbativity can be used to constrain the parameter space from the theoretical side. Our work motivates more extensive research linking primordial features to observable properties of the stochastic background of gravitational waves, and dedicated development in data analysis for their detection.